2017
DOI: 10.1002/lary.26633
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities and comorbidities, not race, affect salivary gland malignancy survival outcomes

Abstract: 4. Laryngoscope, 127:2545-2550, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
5
18
0
Order By: Relevance
“… 12 , 13 Even in 10 and 5 year estimates, lower rates have been reported, ranging from 19.6% to 51% and 35.3% and 65.9%, respectively. 5 , 8 , 9 , 12 , 13 , 16 Higher values have also been presented in the literature. 4 , 17 Ouyang et al 4 presented 5, 10, and 15-year overall survival rates of 84.7%, 70.8%, and 34%, respectively.…”
Section: Discussionmentioning
confidence: 56%
“… 12 , 13 Even in 10 and 5 year estimates, lower rates have been reported, ranging from 19.6% to 51% and 35.3% and 65.9%, respectively. 5 , 8 , 9 , 12 , 13 , 16 Higher values have also been presented in the literature. 4 , 17 Ouyang et al 4 presented 5, 10, and 15-year overall survival rates of 84.7%, 70.8%, and 34%, respectively.…”
Section: Discussionmentioning
confidence: 56%
“…57,63,65,76,77,90 As a result, uninsured patients and patients of low SES or those residing in low SES areas tend to have worse overall and disease-specific survival outcomes. 10,25,59-64,91-98 Women have been shown to have better survival than men for cancers of the oropharynx 32,36,99-101 and some other subsites. 94,101 Two studies indicated that farther distance from a treating facility was associated with improved survival outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we assigned ZIP code tabulation areas (ZCTA) to each patient based upon their home address and utilized these ZCTAs to obtain information about median household income and educational attainment from the 2019 American Community Survey (ACS). 15 Each of these factors reflects information about all households in the ZCTA and are, therefore, only surrogate markers of a patient’s true socioeconomic status (SES). We divided these two factors into quartiles to facilitate analysis.…”
Section: Methodsmentioning
confidence: 99%